Perspektif Fiqh Nawawi Banten dalam Kitab Tafsir Munir - Alify, Moh. Azmi; Arif, Ahmad Imam Puro (Edulaw : Journal of Islamic Law and Yurisprudance, 2024)
There are so many Islamic boarding schools in Indonesia scattered in various regions, from Sumatra to Java, and in Java itself, pesantren are spread from West Java to East Java. There are so many classic books studied by the santri (names of people who study at the pesantren) which discuss Fiqh, Sufism, Tawhid, Tafsir, Hadith and others. This study uses the type of literature study research. Data obtained from documents in the form of books, journals and other reference sources. The data analysis technique used is descriptive data analysis technique. Syekh Nawawi al-Bantani, he is a scholar whose thoughts are very influential in the world of Islamic education in Indonesia, to be precise in Islamic boarding schools. He is a person who truly has extraordinary intelligence so that he is able to contribute in writing books that are used as role models for students. From his point of view, Sheikh Nawawi has a distinctive attitude, one of which is in dealing with the colonial government, he is neither aggressive nor reactionary. However, he was anti-cooperation with the colonial party in any form. He prefers to direct his attention to education, equipping his students with religious zeal and the spirit of upholding the truth. Abstrak Begitu banyak pesantren di Indonesia yang tersebar di berbagai daerah, dari Sumatera hingga Jawa, dan di Jawa sendiri, pesantren tersebar dari Jawa Barat hingga Jawa Timur. Banyak sekali kitab-kitab klasik yang dipelajari oleh para santri (nama-nama orang yang menuntut ilmu di pesantren) yang membahas tentang Fiqh, Tasawuf, Tauhid, Tafsir, Hadist dan lain-lain. Penelitian ini menggunakan jenis penelitian studi pustaka. Data yang diperoleh dari dokumen-dokumen berupa buku, jurnal dan sumber referensi lainnya. Teknik analisis data yang digunakan yakni Teknik analisis data deskriptif. Syekh Nawawi al-Bantani, beliau adalah seorang ulama yang pemikirannya sangat berpengaruh dalam dunia pendidikan Islam di Indonesia, tepatnya di pondok pesantren. Beliau adalah sosok yang benar-benar memiliki kecerdasan yang luar biasa sehingga mampu berkontribusi dalam penulisan buku-buku yang dijadikan panutan bagi para siswa. Dari sudut pandangnya, Syekh Nawawi memiliki sikap yang khas, salah satunya dalam menghadapi pemerintah kolonial, ia tidak agresif maupun reaksioner. Namun, ia anti kerjasama dengan partai kolonial dalam bentuk apapun. Ia lebih suka mengarahkan perhatiannya pada pendidikan, membekali murid-muridnya dengan semangat keagamaan dan semangat menegakkan kebenaran